Farmersâ€™ perception towards dairy farm automation in north India - Meena, H R; Chaudhary, Shalini; Meena, B S; Kadian, K S (Indian Journal of Dairy Science, 2020)
Automation in dairying is operationalized as â€œart and science of utilizing mechanical, electronic equipment and technologies for optimising the production & processing of milk and minimising the need of labourâ€. The study was conducted in five states of northern India. The purpose of this study to assess the commercial dairy farmers perception towards the dairy farm automation technologies. The findings of the study indicated that majority (72.00%) of the farmers considered ICAR, SAU, SVS personal as the most important source of information to update the knowledge on dairy automation/ mechanization technologies. It was found that majority of the farmers considered benefit cost ratio as the most important with mean value of 2.88 prior to purchasing dairy automation/ mechanization technologies. It was also observed that commercial dairy farmers had high scientific orientation, high risk orientation, high level of economic motivation and possessed high innovativeness in their occupation.Â  More than 54.44 percent respondents had high perceptual level, while only 10.00 per cent of the farmers were in the category of low perceptual level. However, 35.56 per cent of the farmers were found in the category of having moderate perceptual level towards dairy automation/ mechanization technologies.